Assessing the acceptability of hormone-based estrus induction / synchronization protocols to overcome anestrus in buffaloes - Mahantswamy, Mallikerimath; Ghuman, Sarvpreet Singh; Singh, Bilawal (Buffalo Bulletin, 2023)
Five hundred dairy households in the rural areas of Punjab state were interviewed through comprehensively designed questionnaires to assess the knowledge and experience of farmers regarding the hormone-based strategies to overcome anestrus and getting the buffaloes pregnant. About 81.8% dairy households were unaware (P<0.05) about any estrus induction or synchronization hormonal protocol and majority (65.5%) of these belonged to households with <5 animals. Out of households having awareness about hormonal protocol use in buffaloes, the majority (58.2%) belonged to households with >15 animal. Out of dairy farmers using hormonal protocols, the proportion of illiterate was 14.8%. Out of dairy farmers not aware about hormonal protocols, the proportion of illiterate was 52.3%. Data analysis of 91 dairy households who had used hormonal protocols revealed summer (65.9%) and anestrus (82%) as the major underlying reasons for their use in buffaloes. Low success rate (20.2%), high cost (50%) and non-availability of doctor (29.7%) were the reasons for the irregular use of hormonal protocols. The success rate of hormonal protocols under field condition in terms of conception was 47.1%. In summary, the major bottlenecks in acceptability of hormone-based therapeutics strategies under filed conditions are illiteracy, high cost of therapeutics strategies and lack of awareness in buffalo farmers especially in households with <5 animals.